Effect of chelated iron activated peroxydisulfate oxidation on perchloroethene-degrading microbial consortium. (March 2021) - McGachy, Lenka; Skarohlid, Radek; Martinec, Marek; Roskova, Zuzana; Smrhova, Tereza; Strejcek, Michal; Uhlik, Ondrej; Marek, Jiri
Abstract: In this work, the effect of In-Situ Chemical Oxidation (ISCO) using peroxydisulfate (PDS) on chloroethenes-degrading microbial consortium in the presence of perchloroethene (PCE; tetrachloroethene) was investigated. Degradation of PCE was examined using PDS without an activation, activated with iron Fe(II) chelated by citric acid (CA), and microbial consortium derived from chloroethenes-contaminated site in liquid and sand microcosms. Two different molar ratios of PCE/PDS/(Fe(II)+CA) (1/8/1.6 and 1/16/3.2) were tested. The PCE removal efficiency was the highest in the bacteria-free microcosms. An expected increase in the PCE removal efficiency by coupling PDS and microbial consortium was not confirmed. Surprisingly, the reduced capacity of PDS to remove PCE in the systems containing both PDS and microbial consortium was observed indicating that indigenous microbes may reduce the efficiency of PDS during a remediation. High-throughput 16S rRNA gene sequencing analysis revealed negative effect of PDS on organohalide-respiring bacteria (OHRB), which were not detected after 19 days of the experiment, unlike in biotic control. On the other hand, amplicon sequence variants (ASVs) affiliated with genera Brevundimonas and Pseudomonas that have been described for their capability of aerobic cometabolic/metabolic degradation of chloroethenes (CEs) were among the most frequently detected ASVs after the PDS treatment. Results further showed that the sole Fe(II)-CA affected the diversity of the microbial consortium. Overall, results of this study provide new insight into the coupling ISCO using PDS with in situ bioremediation of CEs. Graphical abstract: Image 1 Highlights: PCE removal by Fe(II)-CA activated PDS, non-activated PDS, and microbial consortium. Non- and activated PDS negatively affected microbial consortium size and structure. Capacity of the consortium to remove PCE was not impaired significantly. Microbes inhibited PDS efficiency to remove PCE.